(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the integration of subject content and foreign language instruction in higher educational institutions, emphasizing its role in developing foreign language communicative competence among students. The study highlights the benefits of content and language integrated learning (CLIL) approaches and their impact on language proficiency and subject matter understanding. CLIL, which merges content teaching with language education, offers a dynamic and immersive learning environment where students can simultaneously improve their language skills and deepen their knowledge of specific academic subjects. The research delves into the pedagogical frameworks and methodologies that support effective CLIL implementation, such as scaffolding techniques, collaborative learning strategies, and the use of authentic materials. By analyzing case studies from various universities, the article provides insights into the practical challenges and successes associated with CLIL adoption. It also explores how CLIL can be tailored to different academic disciplines, ensuring that both linguistic and content objectives are met without compromising the depth of subject matter coverage.